2012
DOI: 10.1242/jcs.093500
|View full text |Cite
|
Sign up to set email alerts
|

Smad ubiquitination regulatory factor-2 controls gap junction intercellular communication by modulating endocytosis and degradation of connexin43

Abstract: SummaryGap junctions consist of arrays of intercellular channels that enable adjacent cells to communicate both electrically and metabolically. Gap junction channels are made of a family of integral membrane proteins called connexins, of which the best-studied member is connexin43. Gap junctions are dynamic plasma membrane domains, and connexin43 has a high turnover rate in most tissue types. However, the mechanisms involved in the regulation of connexin43 endocytosis and transport to lysosomes are still poorl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 73 publications
(116 reference statements)
3
41
0
Order By: Relevance
“…Depletion of SMURF2 resulted in an overall increase in Cx43 protein levels, in accordance with our previous study (Fig. 2B and Fykerud et al 35 …”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Depletion of SMURF2 resulted in an overall increase in Cx43 protein levels, in accordance with our previous study (Fig. 2B and Fykerud et al 35 …”
Section: Resultssupporting
confidence: 93%
“…We have previously demonstrated that the E3 ubiquitin ligase SMURF2 regulates the endocytosis of Cx43 gap junctions in IAR20 cells under basal conditions and in response to PKC activation 35 . In the present study, we found that SMURF2 has a major role in regulating the endocytosis of Cx43 gap junctions during mitosis in IAR20 cells.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…There is increasing evidence that Cx43 ubiquitination plays an important role in regulating gap junction internalization and degradation and several E3 ubiquitin ligases have been shown to regulate Cx43 internalization from the plasma membrane including TRIM21 69 , Smurf2 70 , and Nedd4 66, 68 . Since these studies were done in cell culture systems, it still remains largely unclear how Cx43 ubiquitination is regulated in the cardiomyocytes.…”
Section: Cx43 Internalization In Healthy Cardiomyocytesmentioning
confidence: 99%